Effects of different soil and water conservation measures on plant functional traits in the Loess Plateau - Duan, Gaohui; Zheng, Cheng; Jiang, Yanmin; Leng, Chunqian; Liu, Yangyang; Wang, Boheng; He, Dianjing; Wen, Zhongming (Frontiers in Plant Science, 2024)
Soil and water conservation measures (SWCM) have a wide-ranging effects on vegetation and soil, and their effects on the ecosystem are mutifaceted, with a complex mechanism. While numerous studies have focused on the impact of such measures on soil, the improvement of plant functional traits is a major factor in the ecological recovery of the Loess Plateau. This survey extensively investigated no measure plots, vegetation measure plots, and engineering measure plots in the Loess Plateau. The impact of SWCM on plant functional traits was investigated using structural equation modeling. We examined six plant functional traits—leaf dry weight (LD), specific leaf area (SLA), leaf tissue density (LTD), leaf total phosphorus (LTP), leaf total nitrogen (LTN), and leaf volume (LV)—correlated with resource acquisition and allocation. In 122 plots, we explored the effects of measures, soil, diversity, and community structure on the weighted average of plant functional trait. The findings showed substantial positive correlations between LD and SLA, LD and LV, SLA and LV, SLA and LTP, LTP and LTN. LTD has a substantial negative correlation with LD, LTD with SLA, and LTD with LV. SWCM limits diversity and the mechanisms by which they affect plant functional traits vary. In structural equation model (SEM) of vegetation measures, improving community structure enhances plant functional traits, but soil factors have the greatest influence on plant functional traits in SEM of engineering measures. Plant functional trait differences on the Loess Plateau result are due to differential plant responses to diverse soil properties and community structure. Vegetation measures enhance the chemical properties of plant functional traits, while engineering measures improve physical properties. The study provides a theoretical foundation for vegetation restoration and management following the implementation of diverse SWCM.